2020
DOI: 10.1101/2020.04.27.062315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disparate temperature-dependent virus – host dynamics for SARS-CoV-2 and SARS-CoV in the human respiratory epithelium

Abstract: 215 words Main text: 2965 words Abstract The human conductive respiratory tract spans a long anatomical distance and represents an important barrier to constrain invading respiratory pathogens. The disparate ambient temperatures found in the upper and lower respiratory tract have been demonstrated to influence the replication kinetics of common cold viruses as well as the associated host responses. Here, we employed the human airway epithelial cell (hAEC) culture model to investigate the impact of ambient temp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
72
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 63 publications
11
72
0
1
Order By: Relevance
“…This delay in the induction of the antiviral response suggests a "too little too late" scenario, where antiviral mechanisms are overwhelmed and subverted by active viral replication. Our findings are compatible with studies showing a limited and/or delayed IFN induction by SARS-CoV-2 as compared to other respiratory viruses, in primary epithelial cells from the airways and the intestine (Blanco-Melo et al, 2020;Lamers et al, 2020;V'kovski et al, 2020;Vanderheiden et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This delay in the induction of the antiviral response suggests a "too little too late" scenario, where antiviral mechanisms are overwhelmed and subverted by active viral replication. Our findings are compatible with studies showing a limited and/or delayed IFN induction by SARS-CoV-2 as compared to other respiratory viruses, in primary epithelial cells from the airways and the intestine (Blanco-Melo et al, 2020;Lamers et al, 2020;V'kovski et al, 2020;Vanderheiden et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…We observed that pretreatment with IFN-b or IFN-l markedly decreased SARS-CoV-2 replication in our reconstituted bronchial epithelium model. These findings are in agreement with studies in various culture systems documenting the inhibitory effect of both type I and type III IFN on SARS-CoV-2 replication, when treatment occurs prior to the stage of massive viral replication (Felgenhauer et al, 2020;Mantlo et al, 2020;Stanifer et al, 2020;V'kovski et al, 2020;Vanderheiden et al, 2020). However, studies in animal models suggest that, at an advanced stage of infection, IFN may contribute to the decline of respiratory function, possibly by worsening inflammation (Boudewijns et al, 2020) and impairing epithelial cell regeneration (Broggi et al, 2020;Major et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Several recent studies have revealed the induction of innate immunity during SARS-CoV-2 infection is dependent on viral growth kinetics and multiplicity of infection. [37,38]. Here, we show that the innate response to SARS-CoV-2 is intact and rapid, as characterized by interferon, chemokine, and IL-6 induction.…”
Section: Discussionmentioning
confidence: 70%
“…Consistently, host responses, such as cytokine expression, that are known to drive inflammation and immunopathologies have been assessed in studies that revealed that SARS-CoV-2 considerably affects the transcriptional landscape of infected cells by inducing inflammatory cytokine and chemokine signatures 38 , 146 , 147 . Although interferon responses have been shown to potently impair SARS-CoV-2 replication, only moderate induction of type I interferon, type II interferon and interferon-stimulated genes was reported 38 , 147 .…”
Section: Coronavirus Biology and Covid-19mentioning
confidence: 99%